A HIGH RATHER THAN LOW PLASMA ADIPONECTIN PREDICTS HIGHER MORTALITY AND MORE ADVERSE CARDIOVASCULAR OUTCOMES IN INFLAMMED PERITONEAL DIALYSIS PATIENTS - Angela Yee-Moon Wang; Christopher Wai-Kei Lam; John E. Sanderson; Iris Hiu-Shuen Chan; Mandy Sea; Siu-Fai Lui; Jean Woo (The Korean Society of Nephrology, 2012)
Plasma adiponectin (ADPN) is markedly elevated in end-stage renal disease (ESRD) patients compared to healthy controls. In this study, we aimed to evaluate clinical correlates of plasma ADPN and its importance in predicting clinical outcomes in chronic peritoneal dialysis (PD) patients. Furthermore, we evaluated the relationship between ADPN and C-reactive protein (CRP) in predicting outcomes of these patients. We prospectively measured plasma ADPN, CRP and other biochemical parameters and body composition in 238 ESRD patients on maintenance PD ≥3 months. Patients were followed for a median of 48 months. The plasma ADPN was 24.6 (13.9, 39.8) and 23.0 (13.9, 32.7)μg/ml for men and women, respectively (P=0.42). Multiple linear regression analysis showed that log-transformed ADPN was correlated with body fat mass (P=0.008), residual glomerular filtration rate (P=0.005), log-CRP (P<0.001), serum albumin (P=0.004), triglyceride (P<0.001) and HDL-cholesterol (P<0.001). Univariate Cox regression analysis showed that plasma ADPN showed no significant association with all-cause mortality and cardiovascular death. However, stratifying patients into 4 groups on the basis of high or low CRP and high or low ADPN (stratified by their median levels), those with high CRP and high ADPN were dialyzed for the longest duration, had the lowest serum albumin, lowest LDL-cholesterol and residual GFR but highest CRP among the four groups. Body mass index and body fat mass were the highest among patients with high CRP, low ADPN. In the multivariable Cox regression analysis controlling for confounding covariates, patients with high CRP and high ADPN showed a 2.33-fold (95% CI, 1.24-4.35; P=0.008) and 2.47-fold (95% CI, 1.09-5.63; P=0.031) increased risk of mortality and cardiovascular death, respectively compared to those with low CRP and high ADPN while those with high CRP and low ADPN were not associated with a significantly increased risk of mortality and cardiovascular death. In conclusion, our data suggests that high rather than low plasma ADPN is predictive of higher mortality and more adverse cardiovascular outcomes in association with inflammation in PD patients.